An update on inflammation in antiphospholipid syndrome. Issue 2 (28th March 2023) - Ambati, Amala; Zuo, Yu; Knight, Jason S.
Abstract : Purpose of review: Antiphospholipid syndrome (APS) is an acquired thrombo-inflammatory disease associated with diverse clinical manifestations in the setting of persistently circulating antiphospholipid antibodies (aPL). This review summarizes recent developments in our understanding of the pathogenesis of APS and its various clinical manifestations with a focus on the activation of endothelial cells, complement, and neutrophils. Recent findings: Elucidating the pathophysiology that leads to the diverse array of clinical manifestations of APS is an area of active exploration. Here, we highlight recent studies that have explored various impacts of endothelial activation and injury in APS, including the promotion of circulating endothelial cells and extracellular vesicles; the association between complement activity and different APS phenotypes, including pregnancy loss; and the relationship between neutrophil extracellular traps (NETs) and high-risk aPL profiles in thrombotic APS. We also call attention to recent work that proposes approaches to mitigating these pathologic changes as potential treatment strategies for APS. Lastly, we highlight promising future directions in APS research, such as multiomics approaches to molecularly stratifying APS patients. Summary: The identification of novel aspects of pathogenesis and more nuanced approaches to phenotyping patients will hopefully pave the way for developing safer and more effective patient-specific therapeutic strategies for APS.